Awareness and education are the most significant elements for safe driving behavior and better life quality - Amal Abdul Aziz Sabri (19772844) (2015)
Traffic has become essential to our daily life. It is necessary to handle it properly by means of prediction, planning and management. This is especially true for the rapid development of road networks in the country and the exponential increase in the number of drivers, vehicles and the related industry development. In recent years, traffic safety, as well as the prevention and treatment of accident injuries have received more attention. In parallel traffic medicine also has appeared as an advanced practical medical concept. Other Information Published in: Journal of Local and Global Health Science, title discontinued as of (2017) License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.5339/jlghs.2015.itma.1